Molecular identification of fungal species infesting tomato (Lycopersicon esculentum) at postharvest phase in Kwanar Gafan, Kano State - Munir Dandago; Alkasim Yunusa; Abdulrashid Rilwan; Sani Yahaya; Shamsudeen Nassarawa; Aliyu Khaleel (Journal of Horticulture and Postharvest Research, 2023)
Purpose: Fungal infections have become the most common problem to cause postharvest loss in tomato enterprise across Nigeria. Morphology-based identification of fungal species usually provides the inconclusive results with several species remain unidentified. Molecular identification method was used to supplement morphology-based techniques to identify the fungal species. Research Method: A Deoxyribonucleic Acid (DNA) through 5.8S-ITS (Internal Transcribed Spacer) region of the ribosomal DNA (rDNA) was used to identify 180 infested tomato specimens. The samples were collected from farm, retail and wholesale points in Kwanar Gafan located at Kura LGA of Kano State. Findings: Eight haplotypes have been detected from the total fungal specimens examined, A 65.6% of fungal specimens from wholesales and farms constituted haplotype-1 and identified as Pichia kudriavzevii (with 99.54% similarity) as BLAST in National Centre for Biotechnology Information (NCBI) database. The remaining seven haplotypes were exclusively found in the retailing points and largely constitutes Aspergillus spp., Mucor fragilis, Russula atroglauca, Ganoderma sp., Alternaria spp., Exserohilum rostratum, Colletotrichum boninense, Naganishia sp. and Cladosporium spp. Research limitations: Further research on molecular identification from other parts of kano is required for better understanding the fungi associated with postharvest loss in the state. Originality/Value: Pichia kudriavzevii is a single and only dominant fungal species that infest tomatoes in both farms and wholesale points (65.6%). However, 34.4% of the diverse fungal species have been found in retailing points which is related to the rapid infestation of tomatoes.